2022
DOI: 10.3390/foods11142007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deacidification Treatment on the Flavor Quality of Zaosu Pear–Kiwifruit Wine

Abstract: Conventional pear–kiwifruit wine has a bland flavor and sour taste, because of excessive l-malic acid content and, consequently, little consumer appeal. An Oenococcus oeni strain, GF-2, has good malolactic fermentation (MLF) performance and high glucosidase activity. Through a Box–Behnken design, the optimum MLF parameters for deacidification by GF-2 were determined: initial pH of 3.4, 5% v/v inoculation, and temperature of 20 °C, which reduced the malic acid content by 98.3%. The changes in the content of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…As acids in fermented wine are mainly transformed from sugars during fermentation, which barely occurs in IBW, the higher concentration of acids in FBW is an important sensory characteristic, but less so in IBW. In general, appropriate concentrations of volatile acids are ideal for producing high-quality wines, and a deacidification treatment could help to improve the flavor quality of FBW [ 21 ]. In addition, more esters would be formed through the esterification of alcohols with organic acids during the fermentation, post-fermentation, and aging processes, which is confirmed by the higher levels of esters in FBW.…”
Section: Resultsmentioning
confidence: 99%
“…As acids in fermented wine are mainly transformed from sugars during fermentation, which barely occurs in IBW, the higher concentration of acids in FBW is an important sensory characteristic, but less so in IBW. In general, appropriate concentrations of volatile acids are ideal for producing high-quality wines, and a deacidification treatment could help to improve the flavor quality of FBW [ 21 ]. In addition, more esters would be formed through the esterification of alcohols with organic acids during the fermentation, post-fermentation, and aging processes, which is confirmed by the higher levels of esters in FBW.…”
Section: Resultsmentioning
confidence: 99%
“…MLF significantly decreased the concentration of organic acids by 29.7% and promoted the accumulation of aromatic esters, higher alcohols, and terpenoids. MLF wine achieved the highest sensory scores for aroma, taste, and overall acceptability [1]. This study indicated that MLF with O. oeni GF-2 had great potential to markedly improve the aroma and taste of commercial pear-kiwifruit wine.…”
mentioning
confidence: 77%
“…However, a biological deacidification method, such as malolactic fermentation (MLF), can significantly reduce the concentration of malic acid and total acidity in wines, without negatively impacting the flavor quality. Yang et al (2022) found that an Oenococcus oeni GF-2 strain had good MLF performance and high glucosidase activity. MLF significantly decreased the concentration of organic acids by 29.7% and promoted the accumulation of aromatic esters, higher alcohols, and terpenoids.…”
mentioning
confidence: 96%
“…Kiwi wine (KW) is a fermented beverage derived from kiwifruit that has a low alcohol content, making it an attractive option for consumers seeking low-alcohol beverages [ 1 ]. Its increasing popularity has led to a growing number of publications on its production, which have determined that the quality of KW is influenced by various factors, including the fermentation strains, raw materials, and pre-treatment methods employed [ 2 , 3 , 4 ]. However, most of these studies focused on KW fermented from peeled and pressed kiwifruits.…”
Section: Introductionmentioning
confidence: 99%